1985
DOI: 10.1080/15287398509530675
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid, bradycardic and hypothermic effects of perfluoro‐n‐decanoic acid in rats

Abstract: A single ip injection of perfluoro-n-decanoic acid (PFDA) to male Wistar rats resulted in an initially rapid, then gradual decrease in food consumption and a parallel loss of body weight. Body temperatures and resting heart rates were significantly depressed by PFDA treatment. As early as 12 h following a single dose of PFDA, serum thyroxine (T4) levels were significantly reduced and remained depressed throughout the 8 day study. Serum triiodothyronine (T3) was reduced by 35% 12 h following PFDA treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The toxicity of this compound is expressed as severe hypophagia, drastic body weight loss with delayed lethality, and thymic and testicular atrophy ( 2 4 ) . It has also been reported that the circulating concentration of L-thyroxine in the rat decreased after administration of PFDA (5,6). Recently, the significance of this hypothyroxinemia was examined by determining the activity of hepatic enzymes responsive to alterations in thyroid status in rats treated with PFDA (7).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The toxicity of this compound is expressed as severe hypophagia, drastic body weight loss with delayed lethality, and thymic and testicular atrophy ( 2 4 ) . It has also been reported that the circulating concentration of L-thyroxine in the rat decreased after administration of PFDA (5,6). Recently, the significance of this hypothyroxinemia was examined by determining the activity of hepatic enzymes responsive to alterations in thyroid status in rats treated with PFDA (7).…”
Section: Introductionmentioning
confidence: 93%
“…Recently, the significance of this hypothyroxinemia was examined by determining the activity of hepatic enzymes responsive to alterations in thyroid status in rats treated with PFDA (7). The incongruous pattern of activity of hepatic enzymes sensitive to thyroid hormone following the administration of PFDA to the rat was, however, not compatible with a decline in thyroid function at the cellular level as might be expected from the reduced level of L-thyroxine in the circulation (5,6). In fact, hepatic activity of malic enzyme (L-malate: NADP oxidoreductase [decarboxylating], EC 1.1.1.40), extensively used as a measure of thyroid hormone effect (&-lo), was markedly increased in PFDA-treated rats (7).…”
Section: Introductionmentioning
confidence: 96%
“…However, these chemicals, which do not exist naturally, are only slightly biodegradable and persist in the environment (Yakata et al 2003). Some overviews of the monitoring and toxicological findings for PFCs (Lau et al 2007;Buck et al 2011;Kannan 2011) include studies of human blood (whole blood, plasma, and serum) (Olsen et al 2003;Kannan et al 2004;Calafat et al 2007) and that of wildlife, including fish, birds, and marine mammals (Tolls et al 1994;Giesy and Kannan 2001;Taniyasu et al 2003;Lehmler 2005;Sinclair et al 2006) as well as of their hepatotoxicity (Klaunig et al 2003;Shipley et al 2004), immunotoxicity (Yang et al 2000;Wan and Badr 2006), hormonal effects (Langley and Pilcher 1985;Maras et al 2006), reproductive toxicity (Peng et al 2010;Stump et al 2008), and developmental toxicity (Olsen et al 2009). …”
mentioning
confidence: 97%
“…Moreover, its serum elimination half-life lasts several years. PFDA has been reported to induce hypophagia and severe weight loss, bradycardia, hypothermia, and decreased serum thyroid hormone levels in rats910. So far, there is certainly a need for more data in the field of PFDA-induced cancers.…”
mentioning
confidence: 99%